Implementasi Prinsip Kehati-Hatian Notaris dalam Pembuatan Akta Perjanjian Perkawinan Yang Berlaku Surut - Risma, Siti; Cahyono, Akhmad Budi (Universitas Batanghari Jambi, 2025)
The research with this title aims to find out the implementation of the precautionary principle which is carried out by a notary in the process of making a retroactive marriage agreement deed, namely an agreement whose process begins after the marriage is carried out. The focus of this research is how the notary applies the precautionary principle so that the agreement does not harm third parties, such as creditors, and ensures that the agreement remains legally valid. In addition, this research also explores the mechanism of making a marriage agreement deed in the realm of still protecting the interests of third parties. The research methodology presented in this study is a normative juridical approach by analyzing relevant laws and regulations, legal doctrines, and case studies. The results show that the prudential principles of notaries include checking the status of assets, notifying related parties, and complying with legal regulations. The mechanism applied by the notary also plays an important role in ensuring that the marriage agreement does not have a detrimental impact on third parties, as well as providing legal certainty for the parties involved. This research provides a conclusion on the application of the precautionary principle by notaries which is a crucial step in maintaining justice and legal certainty, especially in the making of retroactive marriage agreement deeds.